Quality of life of elderly users of long-term health care in and outside the institution - Adnan Osmanspahić; Mile Despotović; Teodora Bošnjak; Goran Mijović; Marija Lukić; Nada Avram; Bojan Joksimović (Биомедицинска истраживања, 2023)
Introduction: Long-term care is series of health and social care services provided at home or in an institutional environment to people with reduced functional capacity. Even though it is known that the quality of life (QoL) of elderly is on a lower level when compared to younger people, there is a small amount of information about QoL of long-term health care patients. The aim of our study was to determine the difference in QoL, depression, anxiety and stress of longterm health care users placed in and outside the institution. Methods: This cross-sectional study included 100 long-term healthcare users, divided in two groups. First group consisted of 50 respondents from primary level of health care and second group consisted of 50 residents of nursing home. The research was conducted in the period from June to July 2022. A general socio-demographic questionnaire, SF-36 health questionnaire for estimating the QoL and the scale of depression, anxiety and stress (DASS-21) were used as instruments in this study. Results: Respondents who were institutionalized had significantly lower values of domains and summary scores of QoL compared to respondents whose health care took place outside of institutions, where the difference was observed in physical health summary score (37.67±6.20% vs. 50.39±10.74%, p<0.001), and the mental health summary score (44.87±11.82% vs. 51.83±16.01%, p =0.015). Respondents who received long-term health care institutionally had significantly (p=0.011) more mild anxiety (12%) and moderate anxiety (34%) compared to respondents who received long-term health care outside the institution (4% vs. 14%). Conclusion: Our results showed that residents of nursing home had significantly worse physical and mental functioning, as well as more frequent occurrence of anxiety symptoms compared to users of longterm health care placed outside institutions, in home environment.
Keywords: quality of life; long-term health care; institution